E-training based on Determination of Education and Training Models of Early Childhood Teachers Education Programs - Siswanto, Yudi; Sutarto, Joko; Mulyono, Sungkowo Edy (Journal of Nonformal Education, 2018)
The success of education and training is determined from all components themselves. E-training as a medium of education and training is one of the aspects of achieving the goals of education and training effectively and efficiently. The purpose of this study is to analyze the e-training based on Determination of Education and Training Models of Early Childhood Teachers Education Programs. This research approach is a quantitative approach using Structural Equation Modeling (SEM). This research was carried out at the Center for Early Childhood Education and Society Education Education in Central Java. The respondents of this study were Early Childhood teachers who attended e-training based education and training which number were 183 respondents in total by using non-probability sampling techniques. Data collection technique used was questionnaire. Data analysis technique was using SEM AMOS software. The results of the study show that individual differences, job analysis and principles of learning indirectly have a positive and insignificant effect on the effectiveness of education and training through the use of e-training. Motivation, active participation, trainer competence, indirect training methods indirectly have a positive and significant effect on the effectiveness of training through the use of e-training. E-training has a positive and significant effect on the effectiveness of training